Key influencing factors analysis on life satisfaction among Chinese older adults with hypertension: a National Cross-Sectional Survey - Wang, Yazhu; Chen, Ziyi; Fan, Heqian; Cao, Shiwei; Wang, Xiaoyu; Niu, Tengfei (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess the current situation and influencing factors of life satisfaction among Chinese older adults with hypertension and to identify its key factors.MethodsIn this study, 4,197 hypertensive patients were selected from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) database for inclusion in the analysis. A multivariate logistic regression model was used to analyze the influencing factors of life satisfaction in hypertensive patients, and the random forest was further used to rank the importance of the significant influencing factors.ResultsOverall, 29.52% of hypertensive patients reported dissatisfaction with their lives. The life satisfaction of these patients was influenced by a combination of factors. According to the results of the random forest, the variables that significantly influenced life satisfaction, in descending order of importance, are self-rated health, economic status, depressive symptoms, sleep duration, fruits, living arrangements, hearing impairment, heart disease, and gender.ConclusionOur research indicates that currently, people with hypertension experience a high level of dissatisfaction with their lives, making it necessary to take preventive and intervention measures from multiple aspects.